Lepton flavor violation in nonholomorphic soft SUSY-breaking scenarios: experimental limits and excesses - M. Rehman; S. Heinemeyer (European Physical Journal C: Particles and Fields)
Abstract We investigate the prospects for the observation of lepton flavor violation (LFV) within the nonholomorphic supersymmetric standard model (NHSSM). We examine charged lepton flavor-violating (cLFV) decays such as such $$μ → e γ $$ μ → e γ , $$τ → e γ $$ τ → e γ and $$τ → μ γ $$ τ → μ γ to impose indirect constraints on both LFV holomorphic and nonholomorphic (NH) soft Supersymmetry-breaking (SSB) terms. These constraints are subsequently utilized to calculate decay rates for LFV Higgs decays (LFVHD). Within the allowed parameter space, NH contributions to LFVHD can be notably larger compared to the holomorphic counterparts. Interestingly, recently ATLAS reported an excess larger than $$2\,σ $$ 2 σ in their searches for $$h → e τ $$ h → e τ and $$h → μ τ $$ h → μ τ . Their best-fit point is not excluded by the corresponding CMS limits. We demonstrate that for some parts of parameter space, the predicted values for $$BR(h→ e τ )$$ BR ( h → e τ ) and $$BR(h→ μ τ )$$ BR ( h → μ τ ) in the NH scenarios reach up to the present experimental limit for these decay processes and can potentially explain the excesses observed by ATLAS, while being in agreement with other experimental constraints. If these decays are eventually observed experimentally, they could potentially serve as a distinctive signature of the NH scenarios and determine some of the NH parameters. Conversely, the limits on the LFVHDs can restrict the allowed parameter space for the NH SSB terms in the NHSSM.